2022
DOI: 10.3389/fmolb.2022.862570
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Microbial Composition in Sepsis-Induced Acute Respiratory Distress Syndrome

Abstract: Background: Acute respiratory distress syndrome (ARDS) is an unresolved challenge in the field of respiratory and critical care, and the changes in the lung microbiome during the development of ARDS and their clinical diagnostic value remain unclear. This study aimed to explore the role of the lung microbiome in disease progression in patients with sepsis-induced ARDS and potential therapeutic targets.Methods: Patients with ARDS were divided into two groups according to the initial site of infection, intrapulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The lung is usually the first target organ attacked by multiple organ dysfunction in sepsis ( 331 , 332 ). The main pathophysiological changes are the destruction of the alveoli-capillary barrier ( 333 ), which leads to increased permeability of pulmonary blood vessels, increased migration of neutrophils to the lungs, and accumulation of protein-rich edema fluid in the alveoli, thus causing tissue and organ damage ( 334 ). Due to the difficulty in balancing the specificity and sensitivity of currently available biomarkers, finding new targeted therapeutic markers is still crucial to prevent ARDS in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The lung is usually the first target organ attacked by multiple organ dysfunction in sepsis ( 331 , 332 ). The main pathophysiological changes are the destruction of the alveoli-capillary barrier ( 333 ), which leads to increased permeability of pulmonary blood vessels, increased migration of neutrophils to the lungs, and accumulation of protein-rich edema fluid in the alveoli, thus causing tissue and organ damage ( 334 ). Due to the difficulty in balancing the specificity and sensitivity of currently available biomarkers, finding new targeted therapeutic markers is still crucial to prevent ARDS in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that different initial sites of infection could influence lung microbiota in patients with septic ARDS. ARDS patients with initial intrapulmonary infection tend to have higher abundance of gut-associated in lung (Zhang et al, 2022). To determine the specific role of gut-lung axis, it is better to make a more nuanced classification in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of gut-associated bacteria, especially Bacteroidetes and Enterobacteriaceae, increased in the lower respiratory tract of ARDS patients (Dickson et al, 2016;Siwicka-Gieroba and Czarko-Wicha, 2020). Further study found that the increase of Escherichia coli in lung was related to higher mortality of ARDS patients (Zhang et al, 2021). Studies have confirmed that the lung microbiota is associated with alveolar inflammation in ARDS (Dickson et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…An interesting complication of ARDS (referred to as “more of the gut in the lung”) is described for critically ill septic ARDS patients [ 81 , 82 , 83 ]. The microbial population in the lungs of ARDS patients can be enriched in gut-associated microbes (more so, in sepsis caused by extrapulmonary rather than intrapulmonary infections) [ 84 ]. Infection of the lungs by gut-associated microbes is attributed to either oropharyngeal aspiration or translocated from the gut [ 81 ].…”
Section: Microbiota Of the Gut And Lungsmentioning
confidence: 99%
“…Infection of the lungs by gut-associated microbes is attributed to either oropharyngeal aspiration or translocated from the gut [ 81 ]. Due to the inter-individual variability and a low-biomass pool, a specific microbial signature for ARDS is lacking [ 84 ]. Nonetheless, a probiotic approach has been explored in mice, yielding promising results [ 85 ].…”
Section: Microbiota Of the Gut And Lungsmentioning
confidence: 99%